Intermodality - Transportation Solution for Global Trade - Hansenova, Heda; Hoa, Ho Thi Thu (Communications - Scientific letters of the University of Zilina, 2006)
World trade has been growing at an average rate which is considerably greater than the growth rate of GDP (Gross Domestic Production). Policies aimed at the reduction of tariffs and quotas have led to an increase in the bilateral trade flows between countries. Increasing global trade also means that opportunities of transportation are growing. The efficient transportation solutions for global trade really offer demand for transport market by sea because of its satisfaction in long-distance routes as well as mass quantity of transported freight. Increasing business relations of two continents EU and Asia (especially ASEAN plus 3 named APT)1) are obviously creating potential trends for transportation network and corridors. One of the very important sea transport routes between ASEAN + 3 and EU can link up the Danube river. While traditional transportation used to separate individual modes of transportation, intermodalism creates unbroken door-to-door transport chains.